2016
DOI: 10.1021/acs.orglett.6b00135
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I)-Catalyzed Cyclization/Nucleophilic Substitution of 1-(N-Sulfonylazetidin-2-yl) Ynones into N-Sulfonylpyrrolin-4-ones

Abstract: Polysubstituted pyrrolin-4-ones have been efficiently synthesized from readily available 1-(N-sulfonylazetidin-2-yl) ynones via gold(I)-catalyzed cyclization/nucleophilic substitution in the presence of various nucleophiles, such as water, alcohols, or indoles. Additionally, 3-iodopyrrolin-4-one derivatives have also been obtained under the same reaction conditions upon addition of 1.2 equiv of N-iodosuccinimide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…A gold-catalysed cyclisation/nucleophilic substitution reaction was recently used by Blanc et al for the synthesis of Nsulfonylpyrroin-4-ones 29 (Scheme 7). [22] Subjection of ynoneazetidines 26 to the reaction condition allowed for an intramolecular cyclisation to form azetidinium intermediates 28. Nucleophilic ring opening of azetidiniums 28 gave the desired N-sulfonylpyrroin-4-ones 29 in moderate to excellent yields.…”
Section: -Membered Ringsmentioning
confidence: 99%
“…A gold-catalysed cyclisation/nucleophilic substitution reaction was recently used by Blanc et al for the synthesis of Nsulfonylpyrroin-4-ones 29 (Scheme 7). [22] Subjection of ynoneazetidines 26 to the reaction condition allowed for an intramolecular cyclisation to form azetidinium intermediates 28. Nucleophilic ring opening of azetidiniums 28 gave the desired N-sulfonylpyrroin-4-ones 29 in moderate to excellent yields.…”
Section: -Membered Ringsmentioning
confidence: 99%
“…[Cy 3 PAu] BF 4 promoted the formation of 2 a in 87 % yield in only 0.5 h (Table , entry 10). Control experiments confirmed that the transformation did not occur in the absence of a gold catalyst, whereas silver tetrafluoroborate alone afforded a minor amount of pyrrolin‐4‐one ( 3 a ) (product type in Scheme , top) along with degradation products (Table , entries 11 and 12). Phenyl 4‐methylbenzenesulfonate was always produced concomitantly in these reactions, thus supporting our mechanistic hypothesis (Scheme ).…”
Section: Methodsmentioning
confidence: 96%
“…We recently demonstrated that bicyclic vinylgold ammonium intermediates, formed by the gold activation of ynones A substituted at the 1‐position with an N ‐sulfonyl azacycle, can be opened regioselectively by oxygenated nucleophiles. This reaction allowed the exclusive formation of pyrrolin‐4‐ones in high yields (Scheme , top) . On this basis, an alternative pathway could be envisaged through nucleophilic attack, either inter‐ or intramolecularly, on the sulfonyl group on the ammonium intermediate B .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations